Comparing multiplier ideals to test ideals on numerically ℚ‐Gorenstein varieties. (23rd February 2015) - de Fernex, Tommaso; Docampo, Roi; Takagi, Shunsuke; Tucker, Kevin
Abstract : We show that the reduction to positive characteristic of the multiplier ideal in the sense of de Fernex and Hacon agrees with the test ideal for infinitely many primes, assuming that the variety is numericallyQ ‐Gorenstein. It follows, in particular, that this reduction property holds in dimension 2 for all normal surfaces.